Assessing the environmental justice of water projects and reforms in the rural south: a co-exploration of institutions and myths. [Abstract only]. - Venot, Jean-Philippe; Clement, Floriane (2010)
Water development projects punctuate the landscapes of the rural South where water sector reforms are endlessly pursued. On the one hand, these new projects and reforms emerge on the ground that they enhance rural livelihoods and are central for food production and sound use of natural resources. On the other hand, the social and environmental inequalities they can induce are often not properly anticipated or recognized. When acknowledged, these effects are attributed to shortcomings in implementation; the remedy is said to be further reforms and projects. In this way, water projects have locked themselves into a 'business as usual' approach, which we argue is unlikely to succeed in delivering equitable water access and control. We do so by investigating the links between procedural (which say do water users have in water development projects?) and distributive justice (how are the benefits distributed?), based on case studies of large irrigation infrastructures in Western India and small reservoirs in West Africa and Eastern India. We draw from the fields of political ecology, development and governance studies and combine institutional and discourse analysis to understand the realities of water projects and their environmental justice dimension. We defend that water projects are grounded in environmental and development narratives that are co-produced by science and policy. Those narratives wield notions of sustainability and justice as universal, hence 'black-boxing' the realities of water resources management. Crucially, and in contrast with the new vocabulary of development, they continue to regard intended beneficiaries as 'recipients' rather than actors with agency. Water projects induce new and multiple claims over resources thus influencing the distribution of goods and bads and related perceptions of justice. Global environmental justice discourses need to recognize that the fairness of any intervention is shaped by, and depends on, the vantage point considered to effectively address current issues of inequality.